Wewenang Mahkamah Syar’iyah dalam Pemeriksaan Praperadilan - Achmad Fikri Oslami (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2022)
Abstract. The Syari'iyah Court is an Islamic Sharia Judicial Institution in Aceh as a Development of the Religious Courts which was inaugurated on 1 Muharram 1424 H/4 March 2003 AD based on Presidential Decree No. 11 of 2003. In accordance with Article 1 paragraph (1) of Presidential Decree No. 11 of 2003 the Religious Court in Aceh Province was changed to a Syar'iyah Court. The Syar'iyah Court has special powers that are different from the Religious Courts outside the province of Aceh. The Syar'iyah Court through Qanun number 6 of 2014 concerning Jinayat Law has the authority to hear cases in the Jinayat field in Aceh. As a consequence of the absolute authority of the Syar'iyah Court in the field of Jinayat, the Syar'iyah Court also handles cases related to Pretrial. Rules regarding Pretrial are regulated in Qanun number 7 of 2013 concerning the Jinayat Procedural Law. The Syar'iyah Court which often handles civil cases is a new thing when faced with pretrial cases. The purpose of this paper is to find out the legality and description of the pretrial examination at the Syar'iyah Court, so as to gain a comprehensive understanding of the process of examining the pretrial case.Abstrak. Mahkamah Syar'iyah adalah Lembaga Peradilan Syari’at Islam di Aceh sebagai Pengembangan dari Peradilan Agama yang diresmikan pada tanggal 1 Muharram 1424 H/ 4 Maret 2003 M berdasarkan Keputusan Presiden Nomor 11 Tahun 2003. Sesuai Pasal 1 ayat (1) Keputusan Presiden RI Nomor 11 Tahun 2003 Pengadilan Agama yang ada di Provinsi Aceh diubah menjadi Mahkamah Syar'iyah. Mahkamah Syar’iyah mempunyai kewenangan khusus yang berbeda dari Pengadilan Agama yang ada di luar provinsi Aceh. Mahkamah Syar;iyah melalu Qanun nomor 6 tahun 2014 tentang Hukum Jinayat berwenang mengadili perkara-perkara di bidang Jinayat di Aceh. Konsekuensi adanya kewenangan absolut Mahkamah Syar;iyah di bidang Jinayat, maka Mahkamah Syar’iyah juga menangani perkara yang terkait Praperadilan. Aturan mengenai Praperadilan di atur di dalam Qanun nomor 7 tahun 2013 tentang Hukum Acara Jinayat. Mahkamah Syar’iyah yang sering menangani perkara perdata menjadi hal yang baru ketika dihadapkan dengan kasus Praperadilan. Tujuan penulisan ini agar dapat mengetahui legalitas dan gambaran pemeriksaan Praperadilan di Mahkamah Syar’iyah, sehingga mendapatkan pemahaman yang komprehensif terkait proses pemeriksaan perkara Praperadilan tersebut.